New defensins from hard and soft ticks: similarities, differences, and phylogenetic analyses - Chrudimská, Tereza; Chrudimský, Tomáš; Golovchenko, Maryna Petrovna; Rudenko, Nataliia Konsta; Grubhoffer, Libor (Veterinary parasitology, 2010)
Despite the importance of ticks as vectors of disease very little is known about their immune system. Antimicrobial peptides, including defensins (phylogenetically ancient antibacterial peptides) are major components of innate immunity in ticks that have been shown to provide protection against gram-negative and gram-positive bacteria, fungi, viruses and protozoan parasites. With the aim of studying the evolution of the genes involved in tick defense, we identified the preprodefensin genes from four Ornithodoros tick species (O. papillipes: isoforms A, B, and D; O. tartakovskyi and O. puertoricensis: isoforms A and B; O. rostratus: isoform A) and from two Dermacentor tick species (D. reticulatus and D. marginatus: one isoform) not previously described. Phylogenetic analyses revealed that Ornithodoros defensin isoforms (A, B, C, and D) form 4 separate clades, while hard tick defensins are divided into several branches based on particular tick species.
Keywords: Molecular Sequence Data; Amino Acid Sequence; fylogeneze; Animals; Defensins; defensiny; klíšťata; zvířata; Ticks; molekulární sekvence - údaje; sekvence aminokyselin; Phylogeny